ANALISIS LEGAL TERHADAP MODAL VENTURA SYARIAH - Dyah widhowaty; Priyonggo Suseno (Peneliti.net, 2023)
The existence of venture capital businesses in Indonesia in the institutional and formal sense is a relatively new legal and business institution which was introduced through the Deregulation Package Policy in 1988 which was followed by the issuance of Presidential Decree No. 61 of 1988. Venture capital plays a role in generating new business models that are believed to make start-ups grow faster and have added value by providing financing and business assistance. In addition, the results of work and innovation produced are more than the old business model. The purpose of writing this article is to describe the legal aspects of Sharia venture capital. The type of research in this article is descriptive research. While the data analysis technique used is a literature study. The partnership between a venture capital firm and a business partner is known as matschaap. The success of this pattern depends on the information transformation process of each party. However, this situation tends to encourage moral hazard, especially by parties who are opportunistic. The main way to mitigate the risk of moral hazard is with a legal agreement and clear legal status.